ENVIRONMENTAL MANAGEMENT EDUCATION: INTERNATIONAL TRADITIONS AND UKRAINIAN EXPERIENCE - Gryshchenko, N. (Проблеми безперервної географічної освіти і картографії)
The paper examines environmental management education experience in the most recognized universities worldwide and compares it with Ukrainian practice. The ratings of the universities are used to make lists of universities to examine. Most of the institutions provide environmental management education in different forms. The study shows that environmental management and related disciplines cover similar topics. American universities use more practical approach and pay more attention to the role of community in decision-making. In Ukraine environmental management courses are taught focusing on management of natural resources, ecological audit, ecological expertise and environmental risk management topics.